ELEMENTAL COMPOSITION OF ROSEMARY SHOOTS (ROSMARINUS OFFICINALIS L.), INTRODUCED IN THE BOTANICAL GARDEN OF PYATIGORSK MEDICAL-PHARMACEUTICAL INSTITUTE - A. S. Nikitina; Z. M. Tohsirova; О. I. Popova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
Nowadays studying plant objects in the framework of environmental monitoring to improve the quality of herbal remedies is a very important area of research.The aim of the work is to determine the elemental composition and assessment of environmental cleanliness of rosemary shoots (Rosmarinus offi cinalis L.), introduced in Botanical garden of Pyatigorsk medical-pharmaceutical Institute (PMPI), Pyatigorsk (Russia).Materials and methods. An experimental study was performed at the Central research laboratories spectral analysis ("Kavkazgeolsyemka") on diffraction spectrograph DFS-8-1 by evaporation from a crater of the carbon electrode. Photometric measurement of spectrograms was performed using the Atlas of spectral lines and spectra of standards with an accuracy of not more than 2% in terms of ash.Results and discussion. For the fi rst time there were 25 elements identifi ed in rosemary shoots introduced in the North Caucasus. The prevailing macro elements were K, Ca, Mg, Na, P and the trace elements were Al, Si and Fe. The toxic elements As, Cd, Hg, Bi, Sb were not detected in the rosemary shoots. Rosemary does not accumulate heavy metals or they are present in trace amounts.Conclusion. The absence of heavy metals or their low content in rosemary shoots can be explained prosperous environmental conditions of Pyatigorsk Botanical garden. The use of rosemary shoots as a source of natural compounds of primary and secondary synthesis and minerals, are involved in the regulation of life processes. This underlines the therapeutic importance of the raw materials and the possibility of creating drugs of combined action on the basis of rosemary for the treatment and prevention of pathologies associated with disorders of mineral metabolism.